Trip Generation Model of Sawah Baru Residential, Ciputat District, South Tangerang Municipality - Adinda Rifqi Aprilliana Haryanta; Verdy Ananda Upa; Eka Apriliasi (Jurnal Poli-Teknologi, 2024)
Traffic congestion in Ciputat area due to increasing of trip generation unsupported by transportation facilities and adequate road network. Generally, solution that implemented is road network capacity upgrades with widening based on trip generation analysis. The purpose of this research to determine trip generation model, total of trip generation, factors that influence of trip generation, and characteristics of trip users on Sawah Baru residence Ciputat Tangerang Selatan. The research method used by household interview survey about number of family members, amount of income per month, number of people working, number of students, number of vehicle owners, amount of transportation costs per month, also trip data from family members daily. Data that has been collected then analyzed with multiple linear regression method used SPSS 25.0 application with significant level 95%. Trip generation model of Sawah Baru residence can be attained Y = 0,450 +0,833 X1 with R2(R square) = 0,833. Total of trip generation that is generated by Sawah Baru residence = 333 trip/day. Based on t Test with significant level <0,05, therefore an influential factors are number of family members, amount of family income, number of people working, number of students, vehicle owners, and transportation cost.